Biochemical characterization, stability, and pathogen safety of a new fibrinogen concentrate (fibryga®). (March 2018) - Schulz, Petra M.; Gehringer, Werner; Nöhring, Sabine; Müller, Sebastian; Schmidt, Torben; Kekeiss-Schertler, Stephanie; Solomon, Cristina; Pock, Katharina; Römisch, Jürgen
Abstract: Fibryga ® is a new lyophilized fibrinogen concentrate for intravenous use for the treatment of congenital fibrinogen deficiency. fibryga ® is produced from pooled human plasma and the final product is characterized by high purity, integrity, and pathogen safety. Functional activity of fibrinogen was demonstrated by cross-linking studies and thromboelastometry; integrity of the fibrinogen molecule was demonstrated by size exclusion chromatography and the detection of only trace amounts of activation markers in the final product. Pathogen safety of fibryga ® was proved by downscaling studies for the two dedicated pathogen inactivation/removal steps, i.e. solvent detergent treatment and nanofiltration. Fibryga ® is stable for at least three years when stored at room temperature. In conclusion, the performed studies demonstrated that fibryga ® meets the requirements for a state-of-the-art fibrinogen concentrate, such as a satisfactory activity profile combined with a favorable pathogen safety profile and stability.